Politinės aplinkos Bulgarijoje įtaka J. Basanavičiui rengiant ir leidžiant “Aušrą” - Visockis, Albinas (Knygotyra, 1995)
Lithuanian national movement was not isolated from analogical processes in Europe in the 18th–19th centuries. All the movements of the nations, which had no self-dependence at that time, had the same or resembling typological traits. The interinfluence was felt. The purpose of this article is to look over the political environment in the Kingdom of Bulgaria, where Jonas Basanavičius was forming as a person and as a politician. The year of 1879, when J. Basanavičius finished his medical studies at the Moscow University, became the year of constitutional monarchy formation in Bulgaria. Life in the country was getting more dynamic because of the adoption of the Tirnov Constitution, the formation of parties, fights among them and frequent changes of governments. Liberalism became one of the most influential political movements in the country. The majority of the intelligentsia who had graduated from higher schools in Russia joined the liberal Party[ies]. Most of them had been students of the Moscow University (e. g. J. Basanavičius and such famous personalities as Petko Karavelov, Dimitr Molov etc.). The ideas of liberalism which especially impressed the representatives of the nations seeking for independence and personal acquaintances brought together J. Basanavičius and liberals. Though formally he wasn’t a member of the Liberal Party but he obviously was its supporter. The removal of liberals from power and their persecution determined J. Basanavičius’ departure from the country. He returned there only when political situation had changed. The war against Serbia (Lom was near the front line, the aggravation of the political situation in Bulgaria and J. Basanavičius’ illness removed him from the “Aušra” from some time. That time coincided with the “Aušra” failure. Later on J. Basanavičius become Bulgarian citizen and joined the Democratic Party which had been originated by consistant liberals under the leadership of P. Karavelov.